Relationship between Family Income and Availability of Basic Sanitation in Stunting Locus - Damar Irza Irza; Laili Rahayuwati; Witdiawati Witdiawati; Raini Diah Susanti; Ahmad Yamin (Universitas Padjadjaran, 2023)
Basic sanitation is influenced by many factors, one of which is welfare. As a component of welfare formation, income directly or indirectly influences sanitation behaviour, impacting a person's health. In children, poor health and nutritional intake are one of the causes of stunting. This study aimed to analyze the relationship between family income and the availability of basic sanitation at a stunting locus, one of which is in a village in Bandung Regency. This research method uses quantitative correlational methods with secondary data analysis. It obtained 204 respondents based on purposive sampling calculations, which were analyzed using the Chi-square test. The study found that the community's income was below the Regency UMK by 58.8%, equivalent to UMK IDR 5,000,000 as much as 38.7%, above IDR 5,000,000 as much as 2.5%. Meanwhile, 77.9% of clean water sources, 70.1% of waste management (latrines) and wastewater, and 5.9% of waste disposal meet the requirements of good condition. The Chi-Square test shows that income has no significant relationship with clean water sources (r=0.448), latrine management (r=0.325), and garbage disposal (r=0.240). So there is no relationship between family income and the availability of basic sanitation, considering that other factors affect the availability of basic sanitation.